Answer
Verified
430.8k+ views
Hint: In order to find the solution to this problem, we will solve according to ${{\left( g\left( x \right) \right)}^{2}}=f\left( a \right)$ format, so we will use formula: $g\left( x \right)=\sqrt{f\left( a \right)},-\sqrt{f\left( a \right)}$ , simplify it and find the value of $x$ accordingly.
Complete step-by-step solution:
We have our equation:
${{\left( 5x-1 \right)}^{2}}=\dfrac{4}{25}$
From the above problem as we can see that it is in the form of ${{\left( g\left( x \right) \right)}^{2}}=f\left( a \right)$ form.
So we will use formula,
$g\left( x \right)=\sqrt{f\left( a \right)},-\sqrt{f\left( a \right)}$
Therefore, evaluate the above formula in our equation, we get:
$5x-1=\sqrt{\dfrac{4}{25}}$
Here we have used the first part of the formula, that is the positive root of the element.
Now, add 1 to both sides, we get:
$5x-1+1=\sqrt{\dfrac{4}{25}}+1$
First let us simplify left hand side:
$\Rightarrow 5x-1+1$
Now on simplifying and by using similar element property, $-1+1=0$
Therefore, we get:
$\Rightarrow 5x$
Now let us simplify right hand side:
$\Rightarrow \sqrt{\dfrac{4}{25}}+1$
On taking out square roots, we get:
$\Rightarrow \dfrac{2}{5}+1$
Now we will convert the element into fractions.
Therefore, we get:
$\Rightarrow \dfrac{2}{5}+\dfrac{5}{5}$
On adding, we get:
$\Rightarrow \dfrac{7}{5}$
Now we will write both right hand side and left hand side:
$5x=\dfrac{7}{5}$
On simplifying:
$x=\dfrac{7}{5\times 5}$
Therefore, we get:
$x=\dfrac{7}{25}$
Now, proceeding to our second part of formula, we get:
$5x-1=-\sqrt{\dfrac{4}{25}}$
Now, add 1 to both sides, we get:
$5x-1+1=-\sqrt{\dfrac{4}{25}}+1$
First let us simplify left hand side:
$\Rightarrow 5x-1+1$
Now on simplifying and by using similar element property, $-1+1=0$
Therefore, we get:
$\Rightarrow 5x$
Now let us simplify right hand side:
$\Rightarrow -\sqrt{\dfrac{4}{25}}+1$
On taking out square roots, we get:
$\Rightarrow -\dfrac{2}{5}+1$
Now we will convert the element into fractions.
Therefore, we get:
$\Rightarrow -\dfrac{2}{5}+\dfrac{5}{5}$
On simplifying, we get:
$\Rightarrow \dfrac{3}{5}$
Now we will write both right hand side and left hand side:
$5x=\dfrac{3}{5}$
On simplifying:
$x=\dfrac{3}{5\times 5}$
Therefore, we get:
$x=\dfrac{3}{25}$
Finally as we can see that we have the value of $x$, that is:
$x=\dfrac{7}{25}$ and $x=\dfrac{3}{25}$.
Note: To find whether the value of $x$ is correct, we can substitute it in the given equation and equate it.
${{\left( 5x-1 \right)}^{2}}=\dfrac{4}{25}$
On substituting $x=\dfrac{7}{25}$ in the left-hand side we get:
$\Rightarrow {{\left( 5\times \dfrac{7}{25}-1 \right)}^{2}}$
Now by applying $BODMAS$ rule, we get:
$\Rightarrow {{\left( \dfrac{7}{5}-1 \right)}^{2}}$
On simplifying and squaring, we get:
$\Rightarrow {{\left( \dfrac{7}{5}-\dfrac{5}{5} \right)}^{2}}$
$\Rightarrow {{\left( \dfrac{7-5}{5} \right)}^{2}}$
$\Rightarrow {{\left( \dfrac{2}{5} \right)}^{2}}$
$\Rightarrow \dfrac{4}{25}$
${{\left( 5x-1 \right)}^{2}}=\dfrac{4}{25}$
Since the left-hand side equals to the right-hand side, we can conclude that the answer is correct.
Complete step-by-step solution:
We have our equation:
${{\left( 5x-1 \right)}^{2}}=\dfrac{4}{25}$
From the above problem as we can see that it is in the form of ${{\left( g\left( x \right) \right)}^{2}}=f\left( a \right)$ form.
So we will use formula,
$g\left( x \right)=\sqrt{f\left( a \right)},-\sqrt{f\left( a \right)}$
Therefore, evaluate the above formula in our equation, we get:
$5x-1=\sqrt{\dfrac{4}{25}}$
Here we have used the first part of the formula, that is the positive root of the element.
Now, add 1 to both sides, we get:
$5x-1+1=\sqrt{\dfrac{4}{25}}+1$
First let us simplify left hand side:
$\Rightarrow 5x-1+1$
Now on simplifying and by using similar element property, $-1+1=0$
Therefore, we get:
$\Rightarrow 5x$
Now let us simplify right hand side:
$\Rightarrow \sqrt{\dfrac{4}{25}}+1$
On taking out square roots, we get:
$\Rightarrow \dfrac{2}{5}+1$
Now we will convert the element into fractions.
Therefore, we get:
$\Rightarrow \dfrac{2}{5}+\dfrac{5}{5}$
On adding, we get:
$\Rightarrow \dfrac{7}{5}$
Now we will write both right hand side and left hand side:
$5x=\dfrac{7}{5}$
On simplifying:
$x=\dfrac{7}{5\times 5}$
Therefore, we get:
$x=\dfrac{7}{25}$
Now, proceeding to our second part of formula, we get:
$5x-1=-\sqrt{\dfrac{4}{25}}$
Now, add 1 to both sides, we get:
$5x-1+1=-\sqrt{\dfrac{4}{25}}+1$
First let us simplify left hand side:
$\Rightarrow 5x-1+1$
Now on simplifying and by using similar element property, $-1+1=0$
Therefore, we get:
$\Rightarrow 5x$
Now let us simplify right hand side:
$\Rightarrow -\sqrt{\dfrac{4}{25}}+1$
On taking out square roots, we get:
$\Rightarrow -\dfrac{2}{5}+1$
Now we will convert the element into fractions.
Therefore, we get:
$\Rightarrow -\dfrac{2}{5}+\dfrac{5}{5}$
On simplifying, we get:
$\Rightarrow \dfrac{3}{5}$
Now we will write both right hand side and left hand side:
$5x=\dfrac{3}{5}$
On simplifying:
$x=\dfrac{3}{5\times 5}$
Therefore, we get:
$x=\dfrac{3}{25}$
Finally as we can see that we have the value of $x$, that is:
$x=\dfrac{7}{25}$ and $x=\dfrac{3}{25}$.
Note: To find whether the value of $x$ is correct, we can substitute it in the given equation and equate it.
${{\left( 5x-1 \right)}^{2}}=\dfrac{4}{25}$
On substituting $x=\dfrac{7}{25}$ in the left-hand side we get:
$\Rightarrow {{\left( 5\times \dfrac{7}{25}-1 \right)}^{2}}$
Now by applying $BODMAS$ rule, we get:
$\Rightarrow {{\left( \dfrac{7}{5}-1 \right)}^{2}}$
On simplifying and squaring, we get:
$\Rightarrow {{\left( \dfrac{7}{5}-\dfrac{5}{5} \right)}^{2}}$
$\Rightarrow {{\left( \dfrac{7-5}{5} \right)}^{2}}$
$\Rightarrow {{\left( \dfrac{2}{5} \right)}^{2}}$
$\Rightarrow \dfrac{4}{25}$
${{\left( 5x-1 \right)}^{2}}=\dfrac{4}{25}$
Since the left-hand side equals to the right-hand side, we can conclude that the answer is correct.
Recently Updated Pages
Fill in the blanks with suitable prepositions Break class 10 english CBSE
Fill in the blanks with suitable articles Tribune is class 10 english CBSE
Rearrange the following words and phrases to form a class 10 english CBSE
Select the opposite of the given word Permit aGive class 10 english CBSE
Fill in the blank with the most appropriate option class 10 english CBSE
Some places have oneline notices Which option is a class 10 english CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
When was Karauli Praja Mandal established 11934 21936 class 10 social science CBSE
Which are the Top 10 Largest Countries of the World?
What is the definite integral of zero a constant b class 12 maths CBSE
Why is steel more elastic than rubber class 11 physics CBSE
Distinguish between the following Ferrous and nonferrous class 9 social science CBSE
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE